Constructing the Meaning of Halal and Tayyib on Social Media: Impacts on the Purchase Intentions of Medan’s Muslim Community - Imai, Mailin; MG, Nashrillah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This study focuses on a qualitative discourse analysis to understand how the concepts of halal and tayyib are constructed and disseminated on social media to influence consumer perceptions. While the study provides a theoretical framework to understand this phenomenon, it does not present quantitative data on the direct increase in consumer purchasing decisions. The findings reveal that social media has transformed how the people of Medan interact with the concepts of halal and tayyib. These platforms serve not only as sources of information but also as spaces for community building and influencing purchasing behavior. For business actors, understanding the dynamics of social media interaction is crucial for developing effective marketing strategies. The study concludes that social media has reshaped the landscape of halal product consumption in Medan. These platforms function as both information hubs and community builders that influence consumer choices. Social, psychological, and technological factors interact in the diffusion process of halal product innovations..